RELATIONSHIP OF NOISE INTENSITY WITH INCREASED BLOOD PRESSURE IN WORKERS IN THE TURBINE AND BOILER AREA MANUFACTURING COMPANY - Wulandari, Suci; Lestari, Mona; Andarini, Desheila; Novrikasari, Novrikasari; Rosyada, Amrina (The Indonesian Journal of Public Health, 2024)
Introduction: Manufacture company is a company focusing on the plantation located in Ogan Ilir Regency. In detail, this company is engaged in the agribusiness of sugar cane plantations and a sugar manufacturing factory. In the production/processing system in the manufacturing company, there is a large noise in the work area, namely the turbine and boiler. These workers are exposed to continuous daily noise in their work environment, which can cause health problems, including increased blood pressure. High blood pressure prevalence in workers exposed to noise levels greater than 75 dB(A) was 82,4%. Aims: To analyze the relation of noise intensity to blood pressure increase in workers in the Turbine and Boiler area of the manufacturing company. Method: The study uses a cross-sectional study. The number sample in this study is 80 workers. Data analysis was using univariate and bivariate analysis with Chi-square and Fisher's exact test. Result: The study shows that the majority of workers' blood pressure is not increased by 46 workers (57.5%) greater than workers whose blood pressure is increased by 34 workers (42.5%). Factors influencing the increase in blood pressure were noise intensity, age, years of service, length of exposure, and ear protection usage, and there is no relationship between smoking habits and sports habits with increased blood pressure. Conclusion: There are five variables related to noise intensity and blood pressure increase, and the area with the highest noise threshold value is the combustion kitchen boiler area.